PELATIHAN IMPLEMENTASI TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) PADA GURU MATA PELAJARAN SMA DI BEKASI - Zarkasih, Enci; Fikrianto, Misbah; Febrianti, Thrisia; Chotimah, Chusnul (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, 2024)
TPACK is a framework concept that emerged as a result of a combination of content, pedagogy, and technology. This concept is the basis for carrying out a learning process through the effective use of technology. This requires the ability of teachers to be able to adapt to environmental changes and the advancement of science and technology. Teachers must be able to integrate ICT components with other learning components to meet the needs of digital learners. With a lot of freely available learning content and technology, it is necessary for teachers to have the ability to integrate the materials, methods, and technologies used. So that the purpose of this PKM activity is to provide training to teachers to implement TPACK in the learning process, especially in integrating content and pedagogics as well as integrating content, pedagogic and technology. Through two trainings carried out by the PKM team to teachers of Sandikta Bekasi Private High School, the results were obtained that there was an increase in teachers' TPACK understanding by 13.22%. This shows that there is a positive impact of TPACK training, especially for subject teachers in integrating content, pedagogic and technology. With this increase in understanding, it is hoped that teachers can apply it in the daily learning process in the classroom.